Interaction of Phytophthora sojae Effector Avr1b With E3 Ubiquitin Ligase GmPUB1 Is Required for Recognition by Soybeans Carrying Phytophthora Resistance Rps1-b and Rps1-k Genes - Li, Shan; Hanlon, Regina; Wise, Hua; Pal, Narinder; Brar, Hargeet; Liao, Chunyu; Gao, Hongyu; Perez, Eli; Zhou, Lecong; Tyler, Brett M.; Bhattacharyya, Madan K. (Frontiers in Plant Science, 2021)
Phytophthora sojae is an oomycete that causes stem and root rot disease in soybean. P. sojae delivers many RxLR effector proteins, including Avr1b, into host cells to promote infection. We show here that Avr1b interacts with the soybean U-box protein, GmPUB1-1, in yeast two-hybrid, pull down, and bimolecular fluorescence complementation (BIFC) assays. GmPUB1-1, and a homeologous copy GmPUB1-2, are induced by infection and encode 403 amino acid proteins with U-Box domains at their N-termini. Non-synonymous mutations in the Avr1b C-terminus that abolish suppression of cell death also abolished the interaction of Avr1b with GmPUB1-1, while deletion of the GmPUB1-1 C-terminus, but not the U box, abolished the interaction. BIFC experiments suggested that the GmPUB1-1-Avr1b complex is targeted to the nucleus. In vitro ubiquitination assays demonstrated that GmPUB1-1 possesses E3 ligase activity. Silencing of the GmPUB1 genes in soybean cotyledons resulted in loss of recognition of Avr1b by gene products encoded by Rps1-b and Rps1-k. The recognition of Avr1k (which did not interact with GmPUB1-1) by Rps1-k plants was not, however, affected following GmPUB1-1 silencing. Furthermore, over-expression of GmPUB1-1 in particle bombardment experiments triggered cell death suggesting that GmPUB1 may be a positive regulator of effector-triggered immunity. In a yeast two-hybrid system, GmPUB1-1 also interacted with a number of other RxLR effectors including Avr1d, while Avr1b and Avr1d interacted with a number of other infection-induced GmPUB proteins, suggesting that the pathogen uses a multiplex of interactions of RxLR effectors with GmPUB proteins to modulate host immunity.